“Pinch technology” for optimisation of palm oil mill operation / Nor Liza Kasim and Zalina Mohd Yusuf - Kasim, Nor Liza; Mohd Yusuf, Zalina (1994)
This field study applies energy, the reduced available work due to change in entropy, to enable enhanced energy use in heat recovery networks. In the process industry, many streams need to be heated or cooled. Heat exchangers and boilers are used to transfer heat between fluid streams. Process heat recovery networks use these arranged in series and parallel to salvage heat that would otherwise be wasted. Current industrial practice is to utilize techniques derived from the First Law of Thermodynamics to achieve an acceptable First Law thermal efficiency for the network. The irreversibilities inherent in energy transformation are not accounted for when applying only the First Law of Thermodynamics. Pinch Technology has been used to formalize a methodology, based on the First Law of Thermodynamics, for the design of heat recovery networks. The Pinch Design Method locates the "Pinch Point" which is the minimum temperature difference separating the hot and cold streams.